Suicide attempt using pure methanol with hospitalization of the patient soon after ingestion: case report - Bucaretchi, Fábio; Capitani, Eduardo Mello De; Madureira, Paulo Roberto de; Cesconetto, Danielle Menezes; Lanaro, Rafael; Vieira, Ronan José (São Paulo Medical Journal, 2009)
CONTEXT: Most patients with methanol poisoning typically show up one to several days after ingestion, presenting severe acidosis, visual disorders, or both. Reports of hospitalization less than 6 h after exposure are unusual. We describe a case of attempted suicide using methanol admitted 3 h after ingestion. CASE REPORT: A 52-year-old male was hospitalized 3 h after intentional ingestion of 150 ml of 99.9% methanol with no co-ingestion of ethanol. He was alert and cooperative, presenting nausea and vertigo, and reporting six episodes of vomiting. Physical examination showed no remarkable features. A blood sample for methanol and ethanol determination was obtained 4 h after ingestion. The result (available 10 h after ingestion) showed 70 mg/dl of methanol, without detectable ethanol. He was treated with a loading dose of 10% ethanol solution (7 ml/kg, intravenously), followed by a maintenance dose of 0.9-1.0 ml/kg/h intravenously (10 to 51 h); hemodialysis (19 to 27 h, together with 2.1 ml/kg/h of 10% ethanol intravenously); and folinic acid intravenously (50 mg every 6 h, from 4 to 51 h). He developed mild/moderate metabolic acidosis without acidemia and was discharged on day four after ophthalmological evaluation and cerebral computed tomography scan, without abnormalities. Follow-up revealed no sequelae. CONCLUSION: This could be classified as a potentially severe case of methanol poisoning, according to the amount and concentration of methanol ingested, and blood methanol concentration at 4 h. The good outcome was attributable to early hospitalization and early antidotal therapy with hemodialysis, starting at 10 and 19 h, respectively.